Analisis Media Pembelajaran Menggunakan Infokus di SD Negeri 136 Pekanbaru - Alya Puspita; Dea Mustika; Deazie Afriani; Widia Sapitri; Gia Arnita (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
The use of technology in elementary school learning plays a crucial role in improving the quality of the educational process. One frequently used tool is the infocus (LCD projector), which serves to present learning materials in visual and audiovisual forms. The purpose of this study was to assess the effectiveness of using infocus-based learning media in elementary schools and its impact on student learning. The method used was a qualitative approach, collecting data through observation, interviews, and documentation. The results showed that the use of infocus can improve students' concentration, motivation, and understanding of the subject matter, as the presentation becomes more engaging and easier to understand. However, the use of infocus in elementary schools still faces various challenges, such as limited facilities and infrastructure, teacher readiness to operate the equipment, and technical problems such as power problems and additional devices. Therefore, supporting facilities and improving teacher skills are needed to ensure the effective and sustainable use of infocus as a learning medium.